FAKTOR YANG MEMPENGARUHI MINAT IBU DALAM PEMILIHAN ALAT KONTRASEPSI SUNTIK - Triswanti, Triswanti; Multazam, Andi Muhammad; Sari, Novi Maya; Apsari, Duhita Dyah (Ensiklopedia of Journal, 2025)
Abstract: Injectable contraceptives are one of the hormonal contraceptive methods applied through injecting drugs directly into the muscle (intra-muscular/IM). Based on observations in the field, it shows that one of the health centers in Semarang City that has many family planning participants who use injectable contraceptives is the Bandarharjo Health Center. It is known that family planning participants in Bandarharjo Health Center tend to prefer to use injectable contraceptives, rather than other types of contraceptives. The purpose of this study was to determine the factors that influence the mother's interest in choosing injectable contraceptives. The research design used in this study was case control. The research was conducted in the Bandarharjo Health Center Working Area. The research was conducted in November 2023. The population is all mothers who use injectable contraceptives at the Bandarharjo Health Center, totaling 125 people. The sample amounted to 126 people who were selected using Total Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between knowledge (p value: 0.032) and there was no relationship between maternal education (p value: 0.650) on the selection of injectable contraceptives. It is recommended for the Puskesmas to increase the frequency of counseling related to contraceptives, especially injectable birth control by involving husbands so that it can provide understanding and make acceptors choose contraceptives more rationally. For family planning acceptors to be able to explore the needs of family planning acceptors and accept if acceptors want to consult the needs of family planning in the family.Keywords: Education, Knowledge, Injections.